Acute toxicity of pyridoxine hydrochloride-containing and noncontaining antituberculosis drugs (an experimental study) - K. I. Usov; G. G. Yushkov; A. V. Mashanov (Туберкулез и болезни лёгких)
This experimental study established DL50 (mg/kg), the degree of toxicity, and a hazard class for 17 antituberculosis drugs (OAO «Farmasintez», Irkutsk). Experiments were performed on experimental biological models: albino outbred rats (n = 3 400) and mice (n = 3 400). The incorporation of pyridoxine hydrochloride into combined antituberculosis drugs was found to considerably decrease their toxicity.